The effect of CH4 and CO2 exposure on carbon nanotubes electrical resistance - Firouzi, Amin; Sobri, Shafreeza; Md. Yasin, Faizah; Ahmadun, Fakhru'l-Razi (Trans Tech Publications, 2011)
This research was carried out to monitor and investigate the gas sensing effects on carbon nanotubes (CNTs) by a systematic study of the variations in the electrical resistance as sensor signal induced by adsorption of CO2 and CH4 gaseous molecules. The CNTs were synthesized by Floating Catalyst Chemical Vapor Deposition (FC-CVD) method on quartz substrate under benzene bubble at temperature of 700°C. Then, they were tested for gas sensing applications operating at room temperature. Upon exposure to gaseous molecules, the electrical resistance of CNTs dramatically increased for both CO2 and CH4 gases with short response time and high sensitivity. It was also observed that the CNTs device behaves as a p-type semiconductor when exposed to gaseous molecules. In addition, the recovery of the sensors and mechanism of gas sensing procedure are discussed.